Prognostic Implication of Platelet Reactivity According to Left Ventricular Systolic Dysfunction Status in Patients Treated With Drug-Eluting Stent Implantation: Analysis of the PTRG-DES Consortium - Han, Donghoon; Kim, Sun-Hwa; Shin, Dong Geum; Kang, Min-Kyung; Choi, Seonghoon; Lee, Namho; Kim, Byeong-Keuk; Joo, Hyung Joon; Chang, Kiyuk; Park, Yongwhi; Song, Young Bin; Ahn, Sung Gyun; et al. (Journal of Korean medical science, 2024)
Coronary artery disease patients undergoing percutaneous coronary intervention (PCI) often exhibit reduced left ventricular ejection fraction (LVEF). However, the impact of LV dysfunction status in conjunction with platelet reactivity on clinical outcomes has not been previously investigated. From the multicenter PTRG-DES (Platelet function and genoType-Related long-term prognosis in DES-treated patients) consortium, the patients were classified as preserved-EF (PEF: LVEF ≥ 50%) and reduced-EF (REF: LVEF< 5 0%) group by echocardiography. Platelet reactivity was measured using VerifyNow P2Y assay and high platelet reactivity (HPR) was defined as PRU ≥ 252. The major adverse cardiac and cerebrovascular events (MACCEs) were a composite of death, myocardial infarction, stent thrombosis and stroke at 5 years after PCI. Major bleeding was defined as Bleeding Academic Research Consortium bleeding types 3-5. A total of 13,160 patients from PTRG-DES, 9,319 (79.6%) patients with the results of both PRU and LVEF were analyzed. The incidence of MACCE and major bleeding was higher in REF group as compared with PEF group (MACCEs: hazard ratio [HR] 2.17, < 0.001, 95% confidence interval [CI] 1.85-2.55; major bleeding: HR 1.78, < 0.001, 95% CI 1.39-2.78). The highest rate of MACCEs was found in patients with REF and HPR, and the difference between the groups was statistically significant (HR 3.14 in REF(+)/HPR(+) vs. PEF(+)/HPR(-) group, < 0.01, 95% CI 2.51-3.91). The frequency of major bleeding was not associated with the HPR in either group. LV dysfunction was associated with an increased incidence of MACCEs and major bleeding in patients who underwent PCI. The HPR status further exhibited significant increase of MACCEs in patients with LV dysfunction in a large, real-world registry. ClinicalTrials.gov Identifier: NCT04734028.